Peran Kepala Madrasah dalam Meningkatkan Kinerja Guru di MI Tarbiyatul Athfal Drajat - Diana Azamul Husna (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
This article discusses the role of the madrasah principal in improving teacher performance within the Islamic educational environment. This study employs a qualitative approach using a case study design. Data collection methods include observation, interviews, and documentation. The focus of the research is on teacher performance at MI Tarbiyatul Athfal, and the data analysis adopts the Miles and Huberman model. The study identified several issues, such as some teachers placing the interests of the madrasah as a secondary priority due to personal matters, family responsibilities, or additional work outside the madrasah. According to several informants, such conditions are understandable from a human perspective; however, if left unaddressed without proper guidance and supervision, they may disrupt the continuity of the educational process in the institution. The proposed solution is for the head of the madrasah to enhance their role through personal and intensive approaches carried out regularly each month, along with consistent mentoring, coaching, and direction for teachers showing a decline in professional commitment. Furthermore, the head of the madrasah must also serve as a role model, an effective communicator, and a facilitator who can create a supportive work environment. Thus, the head of the madrasah holds a central role in fostering discipline, loyalty, and work ethic among teachers through a continuous approach, thereby improving the overall quality of education in the madrasah.